Failure mode of arch structure subjected to internal blast (ST40AB) Focus on experimental study on tracking the debris flight path emanated from explosion - Ng, Melvin Si Yong (2014)
This report focuses on the study to track the flight path of fragmented debris emanating from explosion through experimental and numerical approach. In the event of an explosion, the fragmented debris poses as an adverse effect on the surrounding objects including human beings, causing considerable physical harm and property damage. Despite its high risk characteristic, the flight mechanics of this debris is not well understood. To better understand the fragmented debris flight and its potential risk, it is important to study the dispersal of the fragmented debris, its geometric characteristic and lastly, to identify the impact magnitude by predicting the landing position of the debris subjected to different pressure launching. This report will explain the experimental portion in greater detail. In the experimental study, two approaches were investigated, to establish the continuous measurement technique for tracking the flight path of the debris through a launching experiment. The first approach adopted the use of high speed camera to capture the flight trajectory. The subsequent approach involved the use of inertial measurement sensor to data such as the altitude and position of the airborne projectile during the experiment. Lastly, with the experimental data, numerical modeling was conducted to generate the predicted flight path of the fragmented debris. The numerical analysis was conducted with the use of software, Deflow, developed by Nanyang Technological University.